Structure and chromosomal localization of the gene for the oligodendrocyte-myelin glycoprotein (The Rockefeller University Press, 1990)
Utilizing a cDNA clone encoding the oligodendrocyte-myelin glycoprotein (OMgp) to screen a human genomic DNA library, we have obtained a clone that contains the OMgp gene. The genomic clone was restriction mapped and the OMgp gene and its 5' and 3' flanking regions were sequenced. A single intron is found in the 5' untranslated region of the gene, while the coding region is uninterrupted by an intron. This placement of a single intron in the OMgp gene is identical to that of the gene for the alpha-chain of platelet glycoprotein Ib, which, along with OMgp, belongs to a family of proteins sharing two distinct structural domains: an NH2-terminal cysteine-rich domain and an adjacent domain of tandem leucine-rich repeats. Hence, it is possible that this family of proteins is not only related in terms of primary structure, but also through similar gene structure. Sequence comparison of the 5' and 3' flanking regions did not reveal striking similarities to other DNA sequences, and no obvious promoter elements were noted. By hybridization of the genomic clone to metaphase cells, we have localized the human OMgp gene to chromosome 17 bands q11-12, a region to which the neurofibromatosis type 1 gene has been previously mapped.